Cancelling the apocalypse: Pacific Rim as chthulucinema. Issue 4 (1st October 2020) - Uy, Jamie; Brown, William
ABSTRACT: In this essay, we propose that American sci-fi blockbuster Pacific Rim (Guillermo del Toro, USA, 2013) can be read as an example of chthulucinema. Chthulucinema is a posthumanist cinema that is primarily occupied with notions of the anthropocene and what in Staying With the Trouble, Donna J. Haraway would term the chthulucene– an era in which humans no longer exist as such, and instead either disappear and/or evolve into other lifeforms. In particular, we propose an original argument about drifting, or what Guy Debord characterizes as la dérive, since this move away from the shores of humanity (dé-rive) can be contrasted with the anthropocentric notion of arrival, as seen in other movies featuring aliens, including, of course, Arrival (Denis Villeneuve, USA/Canada, 2016) and, to a certain extent, Avatar (James Cameron, USA, 2009). In other words, we suggest that while Pacific Rim ostensibly rejects the interruption of the other from the outside (humans want to defeat and stop from arriving the alien invaders), formally it depicts the drift of humans away from humanity as fixed and into new, chthulucenic, and malleable identities and dimensions. We do this by considering various aspects of the film and several concepts that it evokes, including hunting, hybridization, and hyperobjects.